PENATAAN JALUR TRACKING DAN PENGEMASAN PAKET WISATA PERDESAAN DESA ADAT PINGE-TUA KECAMATAN MARGA KABUPATEN TABANAN - N. M.,, ARIANI.; SUARDANA, I W. (Buletin Udayana Mengabdi; Vol 8 No 1 (2009): Volume 8 No.1 – April 2009, 2012)
ABSTRACT Activity of settlement of band of tracking in Pinge tourism village have succeeded to arrange band of tracking as long as 1 km widely road 1,5 m. Besides, this band also has competence to be passed by purposely. From result of discussion with elite figures, travel agent and government hence in earning some potency being competent to be sold in the effort of supporting tourism village. Besides, arranging band of tracking owned by Pinge ancient customary village, this activity have succeeded to make package tour and also establish institute of tourism village to control the activity of tourism. The activity of Yoga at Gate of Beji , moreover, becomes a promising package as well as the tourism village. Gate Hill of Cemeng – a traditional village with artistic activity as the example..